The Decoration of the Round Windows of Gagkashen (St. Gregory) Church in Ani - Grigoryan, Diana
Gagkashen Church, constructed during the reign of King Gagik I Bagratuni (989-1017/20) on the occasion of the 1000th anniversary of the birth of Christ, stands out for its architecture among the churches in Ani, the capital of the Bagratid Kingdom. The church (ca. 1001), built by the architect Trdat, was intended to be a recreation of Zvartnots Church dating from 652. Բագրատունյաց մայրաքաղաք Անիում կառուցված եկեղեցիների շարքում առանձնակի նշանակություն է ունեցել Գագկաշեն (Ս. Գրիգոր) եկեղեցին, որը կառուցվել է Գագիկ Ա Բագրատունու (989-1017/20) օրոք` Քրիստոսի ծննդյան 1000-ամյակի առիթով: Տրդատ ճարտարապետի կառուցած եկեղեցում ընդօրինակվել է Զվարթնոցի տաճարի (652) հորինվածքը: Среди церквей, построенных в Ани – столице Багратидского государства, особое место занимала церковь Гагкашен (Сурб Григор), возведенная при царе Гагике I Багратуни (989-1017/20 гг.) по поводу 1000-летия со дня рождения Христа. Церковь, построенная архитектором Трдатом, повторяла композицию храма Звартноц (652 г.).
Keywords: History of Armenian church; Architecture